2018
DOI: 10.1038/s41598-018-25711-2
|View full text |Cite
|
Sign up to set email alerts
|

Naked Gold Nanoparticles and hot Electrons in Water

Abstract: The ionizing radiation in aqueous solutions of gold nanoparticles, stabilized by electrostatic non-covalent intermolecular forces and steric interactions, with antimicrobial compounds, are investigated with picosecond pulse radiolysis techniques. Upon pulse radiolysis of an aqueous solution containing very low concentrations of gold nanoparticles with naked surfaces available in water (not obstructed by chemical bonds), a change to Cerenkov spectrum over a large range of wavelengths are observed and pre-solvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The rate constant of the hydrated electron reaction with DCA is expected to be similar to the acetone reaction (6.5 × 10 9 M −1 s −1 ) [ 25 ]. This observation demonstrates the absence of any primary radical overproduction reported for similar AuNPs by indirect measurements [ 6 , 15 ] or presolvated electron scavenging reported for a higher concentration of AuNPs stabilized by ionic liquids, by both muon methods and pulse radiolysis [ 27 , 28 ]. Previously the absence of • H overproduction in the AuNPs solutions stabilized by ionic liquids was reported [ 28 ].…”
Section: Resultssupporting
confidence: 72%
“…The rate constant of the hydrated electron reaction with DCA is expected to be similar to the acetone reaction (6.5 × 10 9 M −1 s −1 ) [ 25 ]. This observation demonstrates the absence of any primary radical overproduction reported for similar AuNPs by indirect measurements [ 6 , 15 ] or presolvated electron scavenging reported for a higher concentration of AuNPs stabilized by ionic liquids, by both muon methods and pulse radiolysis [ 27 , 28 ]. Previously the absence of • H overproduction in the AuNPs solutions stabilized by ionic liquids was reported [ 28 ].…”
Section: Resultssupporting
confidence: 72%
“…Lastly, we note the recent work by Ghandi et al in 2019 [ 45 ]. This work demonstrated ( Figure 3 ) that extremely dilute (particle concentration = 3.3 × 10 −8 M) aqueous solutions of gold nanoparticles exhibit strong Cherenkov emissions.…”
Section: Historical Overview (1953–1985)mentioning
confidence: 58%
“…Despite being proposed as early as the 1880s by Heviside [ 1 ] and independently by Sommerfield [ 2 ] and Kelvin [ 3 ], at the turn of the 20th century, this work was largely ignored by the scientific community and forgotten until the experimental detection of the phenomenon by Cherenkov and Vavilov in the 1930s [ 4 , 5 ], followed swiftly by a robust theoretical description from Frank and Tamm [ 6 , 7 , 8 , 9 ]. For these latter efforts Cherenkov, Frank, and Tamm were awarded the Nobel Prize in Physics in 1954, and in the decades following, Cherenkov light has seen widespread adoption in a host of various basic science, industrial, and medical fields [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ,…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our group investigated the effects of gravity and an external magnetic field on the hydrothermal synthesis of ZnO nanorods for biosensing applications. [51,52] ZnO nanorods were grown on an indium tin-oxide (ITO) substrate, both against and with gravity, as well as in the presence of various strengths of external magnetic fields. From this, it was shown that the size and morphology of the ZnO nanorods could be altered by the effects of the combined fields, which in turn affected the sensor response to detect bacteria and fungi.…”
Section: Methods Of Synthesismentioning
confidence: 99%